Designing of Technopreneurship Scientific Learning Framework in Vocational-based Higher Education in Indonesia - Hidayat, Hendra; Herawati, Susi; Syahmaidi, Eril; Hidayati, Abna; Ardi, Zadrian (International Journal of Engineering and Technology, 2018)
The complexity of problems at work and high working demands require students to develop multiple skills. One of the alternatives for encountering those conditions is through the process of Entrepreneurship activities or training, especially in vocational-based higher education and other public higher education. This paper aims to present designing process of technopreneurship scientific learning framework in vocational-based higher education. The research used Four D Model (4-D model) which followed stages of 1) Define, 2) Design, 3) Develop, and 4) Disseminate. While in this preliminary research, the stages were conducted only up to the design phase. The framework of technopreneurship scientific learning model resulted consists of, 1) identified problems, needs analysis and learning analysis; 2) scientific technopreneurship cooperative approach; 3) design of the scientific technopreneurship business plan; 4) product (prototype of goods and/or services), and 5) work evaluation. The results elaborate that thetechnopreneurship scientific learning model is as an alternative to producing well-prepared graduates for survival in the society by applying the entrepreneurship skills-based technology.Â